PENGEMBANGAN KAMUS BERBASIS SISTEM OPERASI TELEPON PINTAR PADA MATERI BIOLOGI SMA KELAS XI - Fadli, Rahman; Sartono, Nurmasari; Suryanda, Ade (Jurnal Pendidikan Matematika dan IPA, 2017)
The aim of this study is to produce dictionary based on smartphone operating system in Biology material class XI in Senior High School. The method of research and development adapted from Borg and Gall model. The results of the assessment needed could be concluded that students supported the dictionary based on smartphone operating system’s development. Subject expert, media, and linguist score were 82,33%; 82,85%; and 80%. The average trial test result to students was 76,70% and to Biology teacher was 82,75%. The conclusion is the biology dictionary has very good interpretation level.Keywords: biology dictionary, smartphone, Biology material class XI